Death control in the West 1500-1800 - Hanlon, Gregory, 1953- author.
1 online resource
Keywords: "Employing a rigorous methodological approach and analysing a vast body of sources from towns and regions in Italy, France and England over 300 years, this book hints at the extent of 'routine' infanticide of newborns by married parents in early modern Europe, ignored by contemporary tribunals. This study is an excellent tool for students and researchers interested in the demographic mechanisms of the age and social and familial relationships in early modern Europe"--